LINGKUNGAN "PECINAN" DALAM TATA RUANG KOTA DI JAWA PADA MASA KOLONIAL - Handinoto Handinoto (DIMENSI (Journal of Architecture and Built Environment), 1999)
Pecinan (Chinese Camp) area is never absent in the town of Java. Although the specific characteristics of this mileu is not so strong any more at the present as it was in the past, its presency in diverse smaller towns in Java is still felt as something different. The specific atmosphere of the area, centered on the klenteng as the place of workship, its social environment, included the specific style of house construction, are easy to be recognized. In some world cities like San Fransisco and Manila, the socalled China Towns are just stimulated for its existence. It is even so far, that theyare recomended as tourist destination objects. During the rule of the New Order (1965-1998), Pecinan in the towns in Indonesia are systimatically abolished, because of sicio political considerations. This paper tries to trace back the history of those Chinese Camps in the older towns of Java, to have a certain picture of its existence in the past. Abstract in Bahasa Indonesia : Lingkungan "Pecinan" selalu ada di hampir semua kota-kota di Jawa. Meskipun sekarang lingkungan ini sudah semakin kabur, tapi di beberapa kota kecil di Jawa bekas kehadirannya masih sangat terasa sekali. Atmosfir lingkungannya yang khas, diperkuat dengan kehadiran kelenteng sebagai pusat ibadah dan sosial, serta bentuk-bentuk bangunan yang khas pula sangat mudah untuk ditengarai. Di beberapa kota di dunia seperti San Fransisco, Manila dan sebagainya daerah Pecinan ini justru di perkuat kehadirannya. Bahkan daerah tersebut bisa dijadikan sebagai daerah tujuan wisata kota. Selama Orde baru, karena alasan sosial dan politik, kehadiran Pecinan di kota-kota Indonesia, mulai dihapuskan. Tulisan ini mencoba untuk menelusuri sejarah kehadiran daerah "Pecinan" pada kota-kota di Jawa pada masa lampau. Kata kunci : Kota di Jawa jaman kolonial, Pecinan.